PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP KEPENTINGAN ATAS TANAH YANG DIMOHON BLOKIR MENURUT PERMEN NOMOR 13 TAHUN 2017 TENTANG TATACARA BLOKIR DAN SITA DI BPN KABUPATEN BOYOLALI - IRIANTO, EKO BUDI (Dinamika Hukum, 2019)
The results showed the implementation of legal protection against the interests of the land requested for blocking according to Permen No. 13 of 2017 concerning the Procedure for Blocking and Sita in the BPN of Boyolali Regency, that the party must make a request for registration of the block by specifying as clearly as possible and the willingness to be examined for blocking that is. Some other requirements include: filling out the application form, including a photocopy of identity or power along with the original power of attorney, including a photocopy of the legal establishment deed, information about the name of the right holder, number, area and location of the land requested for blocking, proof of payment of state revenue not tax regarding registration of blocking, and proof of legal relationship between the applicant and the land. Blocking applicants can submit a request letter along with the conditions to the land office office counter. Furthermore, file checking will also be done. If the officer assesses that there is a lack of equipment, the file will be returned to the applicant. Constraints from the blocking applicants and constraints from the internal BPN Office of Boyolali Regency. The constraints of the blocking applicants are the large number of blocking applicants who do not understand the requirements for filing requests for blocking in the BPN Office of Boyolali Regency and on what land status can be blocked. Keywords: Protection, Law, Land Rights, Block